The Impact of Alcohol on the Gut Microbiota: A literature review - Sikora, Jakub; Knychalska, Karolina; Łabuda, Mikołaj; Królikowska, Klaudia; Słojewska, Aleksandra; Kotkowiak, Agata; Sowińska, Teresa; Mentel, Oliwia; Bogucka, Adrianna; Szema, Agnieszka (Journal of Education, Health and Sport, 2025)
Introduction and Purpose The gut microbiota plays a key role in maintaining the body’s homeostasis, influencing metabolic, immunological, and neurological processes. Alcohol consumption, particularly in excessive amounts, disrupts the composition and function of the intestinal microbiota, leading to dysbiosis. This article explores the mechanisms by which alcohol affects the gut microbiota and its consequences for overall health. Additionally, it discusses potential therapeutic strategies aimed at mitigating these negative effects. State of Knowledge Chronic alcohol consumption results in a decrease in the number of beneficial bacteria, such as Lactobacillus and Bifidobacterium, while pathogenic microorganisms increase, which weakens the intestinal barrier and increases inflammatory reactions. Alcohol affects the microbiota through cytotoxic mechanisms, changes in intestinal pH, modulation of the immune system and effects on bacterial metabolism and the gut-brain axis. Alcohol-related gut dysbiosis contributes to the development of a number of conditions, including alcoholic liver disease, metabolic disorders, neurodegenerative diseases and increased cancer risk Conclusion Understanding the impact of alcohol on the gut microbiota is essential for preventing and managing its negative health consequences. Therapeutic approaches such as probiotic and prebiotic supplementation, a fiber-rich diet, and gut microbiota transplantation may help rebalance the gut microbiota and reduce negative effects of alcohol consumption.